A Similarity-Based Hesitant Fuzzy Group Decision Making Approach and Its Application in Hydraulic Engineering Project Management. (12th August 2022) - Zhu, Sulu; Gao, Pengqun; Cheng, Qunzhi; Zhou, Yang; Yang, Shiliang; Zhang, Tianming
Abstract : Hesitancy and uncertainty features of experts are common in the decision-making process, especially for the project management events. To solve this problem, a novel similarity-based decision-making approach is put forward, as well as an application to the hydraulic engineering project management. Several experts, who are invited in the decision-making process, are suggested to adopt hesitant fuzzy preference relations (HFPRs) to show their evaluations. To measure the similarity degree of experts, a novel integrated similarity index ( SI ) is given combining the alternative ranking-based similarity index ( SI AR ) and distance-based similarity index ( SI D ) between HFPRs. The SI AR can be derived from the comparison of the alternative rankings, while the SI D depends on evaluations' distance degree. After that, on the basic of opinion transition probabilities, experts' weights are allocated, which is necessary for the aggregation process. Then, the collective preferences can be aggregated from the individuals' evaluations. Afterwards, the above methods along with a score function are adopted to obtain the optimal solution for an actual hydraulic engineering project management event. Finally, for verifying the feasible and effective features of the presented methods, some significative discussions and comparative analyses are provided.